The physiological quality of ‘Chilli pepper’ seeds, extracted from fruits harvested at different stages of maturation, with and without post-harvest rest - Nakada-Freitas, Pâmela Gomes [UNESP]; de Brito Lima Lanna, Natália; de Lima Silva, Priscilla Nátaly [UNESP]; Bardiviesso, Estefânia Martins [UNESP]; Tavares, Ana Emília Barbosa; Claudio, Marina Toledo Rodrigues; Cardoso, Antonio Ismael Inácio [UNESP]; Magro, Felipe Oliveira; Araújo, Humberto Sampaio (Southern Cross Publishing, 2020)
The objective of this study was to evaluate the physiological quality of ‘Chilli pepper’ seeds, extracted from fruits harvested at different stages of maturation, with and without post-harvest rest. Twelve treatments resulted from the 6 x 2 factorial, with six maturation stages (100% green fruits, 90% green and 10% orange fruits, 10% green and 90% orange fruits, 100% orange fruits, 100% red fruits and 100 % matte red fruits, corresponding to 44, 53, 60, 63, 70 and 73 days after anthesis (DAA), respectively), and fruits with and without rest for seven days. Seeds were evaluated two months after extraction as well as after 14 months of storage in a dry chamber (40% relative humidity and 20°C). The characteristics evaluated were: weight of a thousand seeds, germination, first count, electrical conductivity, emergency test and shoot length of seedlings. Fruits of orange chilli pepper ‘Malagueta’ kept at rest for seven days and bright red fruits and matte without rest produce seeds with physiological quality, which are maintained after a period of 14 months stored in a chamber with 40% relative humidity at 20°C.
Keywords: Capsicum frutescens; Germination; Maturity; Vigor